Enhancing English Language Skills in Higher Education through AI: A Systematic Review of EFL Contexts - Chiqui Vera, Javier Andres; Barragan Mejía , Estefania Nayeli; Zambrano Pachay, Jorge Francisco; Guapacasa Reyes, Roxana Noemí; Acosta Barreno, Jonathan Kevin (Arandu UTIC, 2026)
This study analyzes the integration of Artificial Intelligence (AI) tools in English as a Foreign Language (EFL) teaching within higher education contexts from 2020 to 2025. A systematic literature review was conducted following the PRISMA 2020 protocol. Data were retrieved from the Scopus database, resulting in the selection of 26 empirical studies that met strict inclusion criteria regarding currency, peer review, and pedagogical application. The synthesis reveals a predominance of Generative AI (e.g., ChatGPT) and Automated Writing Evaluation systems (e.g., Grammarly). Findings indicate significant improvements in linguistic competence, particularly in speaking fluency and writing accuracy, alongside positive affective outcomes such as reduced anxiety and increased engagement. However, a paradox of autonomy was identified, highlighting the risk of cognitive offloading where learners may over-rely on AI assistance. The study concludes that AI represents a fundamental shift in pedagogy rather than a mere technological trend. To ensure effectiveness, its implementation requires an approach that emphasizes active teacher mediation, focusing on AI literacy, critical thinking, and process-oriented assessment to foster genuine language acquisition.